Isolation and Identification of Antimicrobial and Cytotoxic Compounds from Garcinia Cantltyna and G. Nigrolineata - Shaker Shadid, Khalid Ahmad (2005)
Eleven species of Garcinia (Guttiferae) from the flora of Malaysia were screened in vitro for antimicrobial and cytotoxic activities. Disc diffusion and MTT methods were utilized to screen the antimicrobial and cytotoxic effects, respectively. On the basis of the screening results and literature review of the tested plants, Garcinia cantleyana and Garcinia nigrolineata were selected for phytochemical investigations. The investigations of the chloroform extract of Garcinia cantleyana by a combination of different chromatographic techniques led to the isolation of eight new natural products: three caged tetraprenylated xanthonoids; cantlyanone A, cantlyanone B and cantlyanone C, four caged triprenylated xanthonoids; cantlyanone D, cantlyanone E, cantlyanone F and cantlyanone G, and 1,4,6,8- tetra hydroxy-5-(2-methyl but-3-en-2-yl)-9H-xanthen-9-one (cantleyanaxanthone). Six known compounds namely, glutin-5-en-3P-01, a mixture of stigmasterol and P-sitosterol, guadichaudion H, garbogiol and for the first time in Garcinia species the isolation of sesquineolignan (Macranthol). All caged-polyprenylated xanthonoids were found to exhibit significant cytotoxicity against several cancer cell lines with IC9 values from 0.2-3 pM. Broth microdilution method was used to determine antibacterial activity for the isolated compounds; the results showed strong antibacterial activity against staphylococcus aureus ATCC 335591 for Cantleyanone F with MIC value of Sesquineolignan (Macranthol) which was isolated for the first time in this genus showed cytotoxic ICS0 values of 4.17, 3.70, 1.53, 2.53 pglml against MDA-MB- 231, MCF-7, CaOV-3 and HeLa, respectively, and antibacterial activity with an MIC value of 3.91 pglml activity against staphylococcus aureus ATCC 335591, the result of which is remarkable. From the methanolic extract of Garcinia nigrolineata leaves, three compounds were isolated, namely a mixture of stigmasterol and P-sitosterol, friedelin, and for the first time methyl putranjivate from Garcinia nigrolineata. Bioassays was carried out, but these compounds were inactive against several cell lines. The structures of all compounds were carried out with the help of chemical and modem spectroscopic techniques (UV, IR, MS, 'H NMR, I3c NMR, DEPT, 'H- "H COSY, HMQC, and HMBC).